The Influence of Women's Leadership Policy on Challenges and Opportunities in the Digital Age - Retno Wulandari, Wahyuni; Ahmad , Nadzriah (Journal of Human Rights, Culture and Legal System, 2025)
The digital era brings significant changes in various aspects of life, including women's leadership. However, gender inequality remains a significant issue in the digital era for women's leadership, so whether current policies have addressed this. This research aims to explore the challenges and opportunities of women's leadership in the digital era and to reformulate policies to bring about justice and equality for women's rights in the workplace. The method used in this research is normative legal research with a legislative, conceptual, and comparative approach with Malaysia to find effective policies for women's rights in leadership positions, especially in this digital era. The research findings indicate that, first, women still face significant challenges, such as gender bias and discrimination, limited access to technology, and workplace imbalance. Secondly, digitalization has created significant opportunities for women to enhance their leadership roles across various sectors, yet persistent gaps in technology access and digital literacy require stronger policy interventions to ensure equal participation. Third,  Strengthening digital literacy, improving digital protection regulations, and fostering collaboration with technology companies are essential strategies for building an inclusive digital ecosystem that empowers women to lead and drive equitable digital transformation.